A study on socio-clinical profile and associated risk factors of stroke patients admitted to neurology department of SCB medical college, Cuttack, Odisha - Mohanty, Minakshi; Sahu, Saswati; Jena, Sushanta K. (International Journal of Research in Medical Sciences, 2021)
Background: Non-communicable diseases (NCDs) are ragging reality of today’s world and have moved up the priority list of most countries worldwide including India. Objectives were to find out prevalence of different types of strokes among the patients admitted in neurology department of SCB medical college, to study socio-clinical profiles of admitted stroke patients and to find out associated risk factors with different types of strokes. Methods: Cross-sectional hospital-based study in neurology ward of SCB MCH, Cuttack, Odisha in 2019-20. Results: The mean age 60.93±12.8, males are more affected, 60-69 years were more affected, 76% were ischemic strokes, 85% cases weakness of limbs reported, hypertension, diabetes, alcoholism, smoking, dyslipidemia were major risk factors. Hypertension and smoking found to be highly significant in case of young stroke patients. Conclusions: Major modifiable risk factors were hypertension (63.3%) followed by alcohol intake 53.9%.